FRAUD AND PRIVACY VIOLATION RISKS IN THE FINANCIAL AGGREGATION INDUSTRY: THE CASE OF REGULATION - Anastassios Gentzoglanis; Avner Levin (European Scientific Journal, ESJ, 2014)
The financial aggregation industry is on the rise again. After having experienced high growth rates during the pre-financial crisis of 2007-2008, the industry has undergone significant changes in terms of structure, behavior and performance. Plagued by lack of trust on behalf of the customers and under the pressure of changing technologies and in the absence of a regulatory framework, new entrants had difficulties in penetrating the market the way have originally anticipated. In the meantime, banks and other financial institutions refined their strategies and consolidated their positions in the new emerging industry. To survive, many early entrants developed new strategies and became suppliers of technology to the banks and other financial institutions. This study uses the SCP paradigm to analyze the emerging financial aggregation industry and the attitudes young customers have toward these services. The results show that customers are seriously concerned with the risks of violation of privacy and fraud associated with aggregation activity online and they are ready to pay a prime to get a more secure service. Nonetheless, regulating of the aggregation industry on the ground of these risks is premature. Yet, the existing regulatory agencies should increase awarness concerning the looming risks and provide incentives to financial aggregators to adopt technologies and operational strategies that minimize the potential for fraudelent behavior online.